Effect of oil pulling on plaque induced gingivitis: A randomized, controlled, triple-blind study - Asokan Sharath; Emmadi Pamela; Chamundeswari Raghuraman (Wolters Kluwer Medknow Publications, 2009)
Background: Oil pulling has been used extensively as a traditional Indian folk remedy for many years for strengthening teeth, gums, and the jaw and to prevent decay, oral malodor, bleeding gums, dryness of the throat, and cracked lips. Aims: The aim of this study was to evaluate the effect of oil pulling with sesame oil on plaque-induced gingivitis and to compare its efficacy with chlorhexidine mouthwash. Materials and Methods : A total of 20 age-matched adolescent boys with plaque-induced gingivitis were selected for this study. They were divided randomly into the study or oil pulling group (Group I) and the control or chlorhexidine group (Group II) with 10 subjects in each group. Plaque index and modified gingival index scores were recorded for the 20 subjects and baseline plaque samples were also collected. The plaque samples were used to identify the microorganisms and to measure the total colony count of the aerobic microorganisms present. The study group was subjected to oil pulling with sesame oil and the control group was given chlorhexidine mouthwash everyday in the morning before brushing. Reassessment of the index scores and collection of plaque for measuring the colony count of the aerobic microorganisms was done after 10 days. Results: There was a statistically significant reduction of the pre- and post-values of the plaque and modified gingival index scores in both the study and control groups ( P < 0.001 in both). There was a considerable reduction in the total colony count of aerobic microorganisms present in both the groups. Conclusion: The oil pulling therapy showed a reduction in the plaque index, modified gingival scores, and total colony count of aerobic microorganisms in the plaque of adolescents with plaque-induced gingivitis.